Developing Survey Methods for Collecting Individual Policy Narratives: A case study of climate change narratives using an engaged convenience sample - Wesley Wehde; Mildred Perreault (International Review of Public Policy)
We examine the assumption of individuals as ‘homo narrans’ and the effect of their demographics and beliefs in shaping policy narratives, using climate change as a case. To do so we use a version of the Narrative Policy Framework codebook to analyze open-ended survey responses in a highly liberal and knowledgeable convenience sample. We use two different ways of collecting narratives in surveys. The first method relies on priming participants to consider certain narrative elements, while the other primes participants to consider the overarching narrative instead of individual elements. In line with public opinion research, we find that conservative ideology and media choices are associated with the use of fewer victims and policy problems. Finally, we find that wording a question in a way that primes overall narratives and problems produces a more reliable result in terms of complete policy narratives than do questions geared toward other narrative elements. We conclude that open-ended survey questions provide a valuable and underutilized, but limited, source of data for scholars interested in the NPF.